African swine fever virus plasmid library: An invaluable resource for research - Machuka, Eunice M.; Gachogo, Rachael; Rodriguez, F.; Lacasta, Anna (International Livestock Research Institute, 2024)
African swine fever virus (ASFV) is a large, complex DNA virus from the family Asfarviridae responsible for African swine fever (ASF), a highly fatal disease affecting domestic and wild pig populations with mortality rates reaching up to 100%. The disease, originally endemic in Africa and Sardinia, has spread globally, leading to significant economic losses. Despite extensive research, no effective commercial vaccine for ASFV is available globally, driving continued efforts to understand the genetic and functional properties of the virus. Plasmids, small circular DNA molecules, play a crucial role in research by enabling cloning, gene expression, and protein production. This report presents the development of an ASFV plasmid library and a corresponding database to support research efforts in ASF vaccine development, gene function analysis, and protein characterization. The library contains plasmids encoding 161 ASFV open reading frames (ORFs) cloned under the control of a CMV promoter. The plasmid collection facilitates antigen screening and functional assays with restriction enzyme sites within the plasmids that can be leveraged for cloning and expression studies, ensuring the versatility and reproducibility of the ASFV research. The development of this plasmid library is a crucial resource for accelerating ASF vaccine research and advancing molecular studies. It also establishes a foundation for its application to other microorganisms, enhancing its utility in broader infectious disease research.